When and how does labour lead to love? The ontogeny and mechanisms of the IKEA effect - Marsh, Lauren E.; Kanngiesser, Patricia; Hood, Bruce (Elsevier, 2018)
We elevate our constructions to a special status in our minds. This ‘IKEA’ effect leads us to believe that our creations are more valuable than items that are identical, but constructed by another. This series of studies utilises a developmental perspective to explore why this bias exists. Study 1 elucidates the ontogeny of the IKEA effect, demonstrating an emerging bias at age 5, corresponding with key developmental milestones in self-concept formation. Study 2 assesses the role of effort, revealing that the IKEA effect is not moderated by the amount of effort invested in the task in 5-to-6-year olds. Finally, Study 3 examines whether feelings of ownership moderate the IKEA effect, finding that ownership alone cannot explain why children value their creations more. Altogether, results from this study series are incompatible with existing theories of the IKEA bias. Instead, we propose a new framework to examine biases in decision making. Perhaps the IKEA effect reflects a link between our creations and our self-concept, emerging at age 5, leading us to value them more positively than others’ creations.